Elevated albumin corrected anion gap is associated with poor in-hospital prognosis in patients with cardiac arrest: A retrospective study based on MIMIC-IV database - Hu, Beiping; Zhong, Lei; Yuan, Meng; Min, Jie; Ye, Lili; Lu, Jianhong; Ji, Xiaowei (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiac arrest(CA) is one of the most leading causes of death. Most of the indicators which used to predict the prognosis of patients with CA are not recognized. Previous studies have suggested that albumin corrected anion gap (ACAG) is associated with recovery of spontaneous circulation in patients with CA, but the predictive value of ACAG for prognosis has not been investigated. This study aims to explore the relationship between ACAG and prognosis during hospitalization in patients with CA. Methods: The baseline data of adult patients with CA hospitalized in the intensive care unit (ICU) from 2008 to 2019 in the American Intensive Care Database (MIMIC-IV, version v2.0) were collected. According to the in-hospital prognosis, patients were divided into survival and non-survival group. Based on the criteria of ACAG level in the previous literature, patients enrolled were divided into normal ACAG (12-20 mmol/L) and high ACAG (> 20 mmol/L) group. The basic information of patients were compared and analyzed between the two groups with propensity score matching (PSM). The Kaplan-Meier method was used to compare the cumulative survival rates of normal and high ACAG groups. Restricted cubic spline (RCS) method and multivariate COX proportional hazards regressions were used to analyze whether elevated ACAG was associated with all-cause mortality during hospitalization. Results: 764 patients were included. A matched cohort (n=310) was obtained after PSM analysis. The mortality rate before and after matching in the high ACAG group was higher than that in the normal ACAG group (P < 0.05;) The Kaplan-Meier survival analysis showed that the cumulative survival rate of the high ACAG group was lower (P < 0.05). RCS analysis showed that ACAG had a non-linear relationship with the risk of in-hospital all-cause mortality (P < 0.001). Multivariate COX regression analysis suggested that elevated ACAG was an independent risk factor for all-cause mortality in patients with CA during hospitalization (P＜0.01). Conclusions: Elevated ACAG is associated with increased all-cause mortality in patients with CA during hospitalization, it can be an independent risk factor for poor prognosis in patients with CA and remind clinicians to pay more attention to these patients.